Autonomy‐Supportive Parenting in Adolescence: Cultural Variability in the Contemporary United States. Issue 1 (26th February 2020) - Benito‐Gomez, Marta; Williams, Kenneshia N.; McCurdy, Amy; Fletcher, Anne C.
Abstract : This review focuses on how the expression of parental autonomy support (particularly the promotion of independence and volitional functioning) and its impact on adolescent adjustment varies across cultural groups in the United States. We review history involving the conceptualization of parental autonomy support and its impact on adolescent development, discuss cross‐cultural research focused on the expression and impact of autonomy support, review theoretical perspectives suggesting the importance of studying variability in parental autonomy support across cultural groups, and summarize research conducted in the United States across four racial/ethnic groups: European American, African American, Latinx, and Asian American. Much of this research does not adequately reflect current understanding regarding the forms of autonomy support, nor is it grounded in theoretical perspectives recognizing the role of culture in shaping parental behaviors. We conclude by discussing directions for further research to overcome existing shortcomings in this literature.